Vermicompostagem: estudo de caso utilizando resíduo orgânico do restaurante universitário da UTFPR Câmpus Curitiba/Sede Ecoville - Nuernberg, Ana Claudia (2014)
The Federal Technological University of Paraná - UTFPR signed the Pact of Agenda 21 in 2010, which states that it aims to reduce the production of waste being sent to landfill. Aiming at the possibility of adequately dispose of waste produced at the University Restaurant - UK UTFPR, this research aimed to develop a vermicomposteira Campus in Curitiba, Ecoville headquarters. During the 02 a 13 December 2013, data were collected as mass and volume of Organic Waste Not Cooked - RONC, as well as the number of meals provided in the UK. The results helped in defining the structure of vermicomposteira, which was built with plastic boxes of 38 L. For each day of the week except Saturday and Sunday, the RONC was divided into six (6) boxes that had holes in the bottom, and were stacked, with a box without holes in the base to collect manure produced. From 16 to 30 April 2014 was started ambiance of earthworms, and between 05 a May 30, 2014 started vermicomposting, with daily addition of fresh RONC produced by the UK. On June 10, 2014 were collected 5 samples of the compound of each box, in order to compose a sample that represented each weekday. These samples were sent for analysis macro and micronutrients and Carbon Nitrogen ratio - C/N, in the laboratory of the Department of Soil Science of the Federal University of Paraná soils. Were composted in all 477.97 kg which included RONC, coffee grounds and tea and dried leaves, avoided by the addition of citrus peels in this phase of the research. After 56 days of activity was noted that compound was close to humification in phase with an average C/N ratio of 13.48 / 1. The values and limits for marketing compound were compared with the Instruction - IN the Agriculture Defense Department No. 25 of 2009. Phosphorus and Potassium had no reference values in IN, and the amount of calcium and magnesium were within the limits the respective set. The micronutrients, the compound appeared rich in Iron and Boron, but showed values below the type recommended as the zinc, and were not detected the elements of Manganese and Copper. The IN No. 25 of 2009 does not provide reference values for aluminum. During the period of vermicomposting held for research, approximately 1,942 m3 of organic waste, equivalent to 28% of the total generated in Ecoville headquarters are no longer sent to the landfill, resulting in 288.8 pounds of fertilizer in the form of humus and 94 liters of concentrate liquid manure slurry. The vermicomposting technique in boxes is efficient for use in environments with little space available, but it is still necessary to continue research to establish a better balance between C/N to produce less manure.